The combination of tetramethylpyrazine and vitamin A acid in the treatment of skin photoaging by activating the HIF-1α pathway: TMP and vitamin A acid in skin photoaging - Chen, Weijun; Fan, Jianyong; Zou, Xuelian; Wu, Yuansheng (Cellular and Molecular Biology, 2024)
Skin photoaging is a skin degenerative disease that causes patients to develop malignant tumors. The existing clinical treatment of photoaging has limitations. This greatly reduces the recovery rate of photoaging patients. Studies have confirmed that Ligusticum wallichii Franch (LWF) monomer tetramethylpyrazine (TMP) alleviates various skin diseases. The combination of traditional Chinese medicine and Western medicine helps with this process. Our research aimed to explore the specific treatment mode and molecular mechanism of TMP in treating skin photoaging. CCK-8 assays were used to evaluate the activity and toxicity of HaCaT cells. β-galactosidase aging, Carbonyl compound and nitrosylated tyrosine assays were used to analyze the aging of HaCaT cells. ROS assays and ELISA were used to analyze the enrichment of ROS. The molecular docking experiment analyzed the binding of TMP and HIF-1α. qRT-PCR and Western blot were used to detect the activation of skin aging-related pathways. HE staining was used to analyze the thickness of the stratum corneum skin on the back skin of mice. 200μg/L LWF alleviates cellular photoaging and mouse skin photoaging by reducing ROS enrichment. Its monomer TMP plays an important role in this process. The combination of TMP and HIF-1α accelerates the degradation of ROS by activating the Nrf2/ARE signaling pathway. This process reduces the apoptosis of cells damaged by light. In addition, we also found that the combination of TMP and retinoic acid (RA) is more beneficial for the treatment of skin damage caused by light in mice. The combination therapy of TMP and RA alleviates skin oxidative stress response through overexpression of HIF-1α. This plan is beneficial for the treatment of skin photoaging.